Adrenal haemorrhage and infarction in the setting of vaccine-induced immune thrombocytopenia and thrombosis after SARS-CoV-2 (Oxford–AstraZeneca) vaccination. (10th February 2022) - Graf, Anneke; Armeni, Eleni; Dickinson, Louise; Stubbs, Matthew; Craven, Brian; Srirangalingam, Umasuthan; Chung, Teng-Teng
Abstract : Summary: Rare cases of vaccine-induced Immune thrombocytopenia and thrombosis (VITT) are being identified after vaccination with the SARS-CoV-2 Oxford–AstraZeneca vaccination. We report on two such patients with associated adrenal involvement, which is now being recognised. Both patients presented with abdominal pain, back pain and vomiting. Case 1 was a 46-year-old male who had received the first dose of the Oxford–AstraZeneca vaccination 8 days earlier. Imaging demonstrated a number of serious thrombotic complications including evolving bilateral adrenal haemorrhage (right adrenal haemorrhage identified at presentation, with the left-sided changes only evident on day 4 of the admission). Case 2 was a 38-year-old female who had received the first dose of Oxford–AstraZeneca vaccination 11 days prior. Imaging demonstrated left renal vein thrombosis and left adrenal infarction. VITT was diagnosed in both cases given these changes and other consistent haematological findings. Both patients were treated empirically for adrenal insufficiency, a diagnosis subsequently confirmed in case 1. We report these two cases of VITT presenting with adrenal complications (haemorrhage and infarction) after Oxford–AstraZeneca vaccination to highlight the association and the need for prompt management of co-existing adrenal insufficiency, especially given the potential for evolving adrenal involvement. Learning points: Adrenal complications (thrombosis/infarction/haemorrhage) may develop as a part of vaccine-induced immune thrombocytopenia (VITT) after SARS-CoV-2 Oxford–AstraZeneca vaccination. Evolving adrenal involvement is possible and ongoing assessment is required to identify this promptly. Cortisol levels may be difficult to interpret when assessing for adrenal insufficiency, given high doses of corticosteroids may be used to manage VITT. Clinicians should have a low threshold for starting empirical replacement with corticosteroids until reliable assessment of adrenal function can be performed.